2012
DOI: 10.3748/wjg.v18.i13.1525
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Parameters and hepatic fibrosis scores in children with nonalcoholic fatty liver disease

Abstract: APRI and FIB4 might be useful noninvasive hepatic fibrosis scores for predicting hepatic fibrosis in children with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 28 publications
2
95
1
2
Order By: Relevance
“…INR values were not recorded as the majority of patients were on warfarin therapy. Several scores found to be predictive of hepatic fibrosis in other patient populations (7)(8)(9) were calculated including AST to ALT ratio (7), APRI (AST to platelet ratio) (8) and FIB-4 score (age*AST/platelet count*ALT) (9).…”
Section: Methodsmentioning
confidence: 99%
“…INR values were not recorded as the majority of patients were on warfarin therapy. Several scores found to be predictive of hepatic fibrosis in other patient populations (7)(8)(9) were calculated including AST to ALT ratio (7), APRI (AST to platelet ratio) (8) and FIB-4 score (age*AST/platelet count*ALT) (9).…”
Section: Methodsmentioning
confidence: 99%
“…Recently published studies have shown that the sensitivity of the APRI index depends on the etiology of the chronic liver disease: its accuracy is acceptable for assessing liver fibrosis in patients with cHCV and NAFLD, but not for cHBV (129,131,169,170). Interestingly protease inhibitor-based cART was protective (111,116 (116).…”
Section: Ast-to-platelet Ratio Indexmentioning
confidence: 99%
“…In studies in HIV-infected adults, it has been found to 112 be a useful predictor of liver disease, HCC and even risk of mortality. In children, the FIB-4 score has not been validated although a few studies among children with NAFLD and HIV have been published (23,110,(128)(129)(130)(131)172). …”
Section: Fibrosis-4 Scorementioning
confidence: 99%
“…Considering the importance of continuous monitoring of liver structure in children and infants with chronic liver disease and also avoiding several liver sampling because of its consequences, the application of noninvasive procedure for the proper treatment is essential. Because few studies have been conducted on the relationship of laboratory markers and indices of fibrosis in children with chronic liver diseases (Kim et al 2010;Breton et al 2009;Yang et al 2012;Della Corte et al 2011), we decided to perform this study in children referred for liver transplantation in Shiraz, Iran.…”
Section: Introductionmentioning
confidence: 99%